ARAB WOMEN IN THE MIDDLE EAST AND THE LABOR MARKET: BARRIERS AND OBSTACLES TO CHOOSING A PROFESSION - Balous, Lulu (E-Journal VFU, 2025)
Arab women in the Middle East continue to face substantial barriers in their pursuit of professional careers. Despite notable advances in women’s educational attainment and the expansion of legal frameworks formally promoting gender equality, women’s participation in the labor market remains persistently low. This paper examines the structural obstacles that constrain Arab women’s ability to choose, enter, and advance in professional careers. Drawing on interdisciplinary literature from gender studies, sociology, economics, and development studies, the analysis highlights how cultural norms, legal and institutional arrangements, workplace discrimination, economic dependency, and weak support structures interact to reproduce gender inequality. Adopting a critical structural perspective, the paper argues that women’s underrepresentation in employment is not a function of individual choice or capability, but rather the outcome of cumulative and intersecting constraints embedded within social, economic, and political systems. The paper concludes by proposing multi-level policy interventions addressing legal reform, labor market institutions, educational alignment, and cultural transformation, emphasizing that women’s economic empowerment constitutes a structural prerequisite for social justice and sustainable development in the Middle East
Keywords: Arab women; Gender inequality; Labor market participation; Structural barriers; Economic dependency; Education–employment mismatch; Women’s empowerment; Middle East